A cyclopeptide and three oligomycin-class polyketides produced by an underexplored actinomycete of the genus Pseudosporangium - Shun Saito; Kota Atsumi; Tao Zhou; Keisuke Fukaya; Daisuke Urabe; Naoya Oku; Md. Rokon Ul Karim; Hisayuki Komaki; Yasuhiro Igarashi (Beilstein Journal of Organic Chemistry, 2020)
Aside from the well-studied conventional actinomycetes such as Streptomyces, the less investigated genera of actinomycetes also represent a promising source of natural products. Genome mining indicated that members of the underexplored genus Pseudosporangium, from which no secondary metabolites have been reported to date, may harbor the biosynthetic machinery for the formation of novel natural products. The strain RD062863, that is available at a public culture collection, was obtained and subjected to metabolite analysis, which resulted in the discovery of a novel cyclopeptide, pseudosporamide (1), along with three new oligomycin-class polyketides, pseudosporamicins A–C (2–4). The unusual structure of compound 1, featured by a biaryl-bond bridging across a tripeptide scaffold, N-acetyl-ʟ-Tyr-ʟ-Pro-ʟ-Trp, was determined by a combination of spectroscopic analyses, chemical derivatization, ECD calculation, and DFT-based theoretical chemical shift calculation, revealing the presence of an (Sa)-axial chirality around the biaryl bond. Compounds 2–4 lacked hydroxylation on the side chain of the spiroacetal rings, which showed clear contrast to other oligomycin congeners and related polyketides with ring-truncation or expansion. The new macrolides 2–4 displayed potent antimicrobial activity against the Gram-positive bacterium Kocuria rhizohpila and the plant pathogenic fungus Glomerella cingulata. All compounds showed moderate cytotoxicity against P388 murine leukemia cells with IC50 values in the micromolar to submicromolar ranges. These results exemplified the validity of phylogeny-focused strain selection combined with biosynthetic gene-directed genome mining for the efficient discovery of new natural products.